How Soviet “Legitimacy” Was Made: 1940 “Elections” in Occupied Latvia - Gints Zelmenis (Review (Institute of National Remembrance), 2023)
The Soviet occupation of Latvia in 1940 was “legitimized” by “People’s Saeima” which was “elected” on July 14–15, 1940. A significant role in these “elections” was carried out by The Communist Party of Latvia, which at that time was a branch of Comintern and therefore acted as a Soviet agency in Latvia. Some two dozens of candidates for MP of the “Working People’s Bloc” (which was openly backed by USSR officials) were at the same time members of various electoral commissions. “People’s Government”, which was appointed after the occupation of Latvia, Central Election Commission, local communists and their supporters were just executors in these “elections”. The real “master of puppets” who supervised whole process was Deputy Chairman of the Soviet government Andrey Vyshinsky and some other Soviet officials. These “elections” had nothing to do with elections in the common, democratic sense of that word. In fact, it was an affair of misleading, intimidation and fraud on a large scale. These events had grave consequences for Latvia – the loss of independence and establishment of extremely repressive regime in all three Baltic states.